Fluctuating nonlinear oscillators from nanomechanics to quantum superconducting circuits - Dykman, Mark. (Oxford : Oxford University Press, 2012)
This text provides a unifying insight into fluctuation phenomena in a broad variety of vibrational systems of current interest. It consists of individual chapters written by leading experts in the field. The chapters are self-contained and complement each other.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Nonlinear oscillators; Fluctuations (Physics)